PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA FISIK DAN PENGEMBANGAN SDM TERHADAP KINERJA PEGAWAI PADA BADAN KESBANGPOL PROVINSI SUMATERA BARAT - Pasaribu, Dina Rahmatika Br; Martha, Lidya (Ensiklopedia of Journal, 2025)
Abstract Financial performance is a description of an achievement or result of a Employee performance is the work results achieved by employees in accordance with the responsibilities given to them. The aim of this research is to determine and analyze the influence of organizational culture, work environment and human resource (HR) development on employee performance. This type of research is quantitative. This research was conducted at the National and Political Unity Agency (Kesbagpol) of West Sumatra province. The data analysis technique for this research is using SPSS. The sampling technique used in this research is probability sampling. The sample for this research was 35 employees. The results of this research state that organizational culture, work environment and human resource (HR) development have a positive and significant effect on employee performance.Keywords: Organizational Culture, Work Environment, Human Resources (HR) Development, Employee Performance